Poly (ADP-ribose) polymerase inhibitors selectively induce cytotoxicity in TCF3-HLF–positive leukemic cells. (1st February 2017) - Piao, Jinhua; Takai, Shiori; Kamiya, Takahiro; Inukai, Takeshi; Sugita, Kanji; Ohyashiki, Kazuma; Delia, Domenico; Masutani, Mitsuko; Mizutani, Shuki; Takagi, Masatoshi
Abstract: Poly (ADP-ribose) polymerase (PARP) is an indispensable component of the DNA repair machinery. PARP inhibitors are used as cutting-edge treatments for patients with homologous recombination repair (HRR)-defective breast cancers harboring mutations in BRCA1 or BRCA2 . Other tumors defective in HRR, including some hematological malignancies, are predicted to be good candidates for treatment with PARP inhibitors. Screening of leukemia-derived cell lines revealed that lymphoid lineage–derived leukemia cell lines, except for those derived from mature B cells and KMT2A ( MLL )-rearranged B-cell precursors, were relatively sensitive to PARP inhibitors. By contrast, acute myelogenous leukemia cell lines, except for RUNX1-RUNXT1 (AML1-ETO)-positive lines, were relatively resistant. Intriguingly, TCF3 (E2A)-HLF–positive leukemia was sensitive to PARP inhibitors. TCF3-HLF expression suppressed HRR activity, suggesting that PARP inhibitor treatment induced synthetic lethality. Furthermore, TCF3-HLF expression decreased levels of MCPH1, which regulates the expression of BRCA1, resulting in attenuation of HRR activity. The PARP inhibitor olaparib was also effective in an in vivo xenograft model. Our results suggest a novel therapeutic approach for treating refractory leukemia, particularly the TCF3-HLF–positive subtype. Highlights: TCF3 (E2A)-HLF-positive leukemia exhibits sensitivity to PARP inhibitor. TCF3-HLF expression suppressed homologous recombination repair activity. TCF3-HLF expression suppressed MCPH1 level.